Application of modular ortho-massage system in early post-operative therapy - Sarnov, Igor (Global Prosperity, 2025)
Abstract. The article focuses on examining the effectiveness of using a modular ortho-massage system as part of early postoperative therapy to improve rehabilitation outcomes and clinical results. The aim of the study is to justify the use of a modular ortho-massage system as a component of early postoperative therapy for enhancing clinical outcomes and accelerating patient recovery. The study employed general scientific methods of cognition, including analysis, synthesis, comparison, induction, deduction, systematization, and generalization. The findings demonstrate that implementing ortho-massage therapy during the early postoperative period is a relevant direction in modern medical rehabilitation, grounded in the principles of a multidisciplinary approach and personalized medicine. Massage therapy contributes to reducing pain, relieving muscle tension, and stabilizing patients’ psycho-emotional condition, which collectively promotes faster healing after surgery and supports an earlier return to functional activity. The inclusion of massage in a comprehensive mobilization system, which also involves physical activity, electrical stimulation, and muscle relaxation, produces a pronounced synergistic effect and decreases the likelihood of complications. The study shows that within 7 to 21 days after surgery, patients receiving massage therapy exhibit positive progress. The effectiveness of autonomous mechanical systems, particularly TISA Neuro-Ortho Therapy and exoskeletal massage modules, was also explored, revealing their beneficial impact even for patients with limited access to standard physical rehabilitation. The practical value of this research lies in the potential integration of modular ortho-massage systems as an effective rehabilitation tool in clinical postoperative care.